Comparative Analysis Of Accelerometer Sensor And Piezoelectric Sensor Capabilities In The Early Warning System Earthquake Disaster - Manuel, Yoses; Widodo, Kartiko Ardi; Palevi, Bima Romadhon (Universitas Nurul Jadid, 2025)
An earthquake is a vibration or shock caused by a sudden release of energy from within the earth, which produces seismic waves. The Indonesian region is currently vulnerable to volcanic and tectonic earthquakes due to the Pacific Ring of Fire, where the Indo-Australian tectonic plate collides with the Pacific tectonic plate. So this study aims to conduct a comparative analysis between earthquake disaster early warning systems that use sensors Accelerometers and Piezoelectric sensors. The two types of sensors used are an Accelerometer IMU 9 DOF to measure the acceleration of ground motion and a Piezoelectric sensor to measure vibration. Using the ESP32 which processes sensor data and sends data to Google Sheets using the Wi-FI module in real-time. Sampling data from the readings of each sensor will be used to determine the most accurate use of sensors for detecting earthquakes. In the results of the comparison of the two sensors, the average percentage of errors where the sensor Accelerometer with an error of 0.104% and a piezoelectric sensor with an error of 100% so that it can be concluded that the Accelerometer sensor is more accurate than the piezoelectric.